2018
DOI: 10.1111/iej.12981
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and immunoexpression of FGF‐1 and Ki‐67 in rat subcutaneous tissue following the implantation of Biodentine and MTA Angelus

Abstract: The collagen-rich capsule formed slowly around Biodentine in comparison with MTA. FGF-1 and mast cells participated in capsule remodelling, stimulating fibroblast proliferation and subsequent collagen production, in response to subcutaneous implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…The CE-1 sealer had a reduced inflammatory infiltrated when compared to AH Plus, showing a connective tissue with scarce inflammatory cells dispersed amongst collagen fibres and fibroblasts. The presence of fibroblasts in the 60-day period indicates progressive tissue repair (Silva et al 2015, da Fonseca et al 2019. Zordan-Bronzel et al (2019) demonstrated that the experimental sealer used in this study was cytocompatible with potential for use as a root canal filling material.…”
Section: --mentioning
confidence: 77%
“…The CE-1 sealer had a reduced inflammatory infiltrated when compared to AH Plus, showing a connective tissue with scarce inflammatory cells dispersed amongst collagen fibres and fibroblasts. The presence of fibroblasts in the 60-day period indicates progressive tissue repair (Silva et al 2015, da Fonseca et al 2019. Zordan-Bronzel et al (2019) demonstrated that the experimental sealer used in this study was cytocompatible with potential for use as a root canal filling material.…”
Section: --mentioning
confidence: 77%
“…Previous reports have focused on whether Biodentine or MTA may cause inflammation (da Fonseca et al . 2016, 2019) or how normal tissues react to the presence of either Biodentine or MTA (Miller et al . 2018, Giraud et al .…”
Section: Discussionmentioning
confidence: 99%
“…Biodentine (Septodont Inc., Saint‐Maur‐des‐Fossés, France) is used during pulp capping and REPs. Biodentine is not only biocompatible (da Fonseca et al . 2019) but also bioinductive when applied to dental tissues (Miller et al . 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The thicknesses of apical plugs and different irrigation agents are reported to affect the apical leakage. Twelve millimeters of Bioaggregate exhibits the best resistance to leakage while Ethylenediaminetetraacetic acid (EDTA) and a Shahi et al, 2010;Cintra et al, 2013;Bueno et al, 2019 • Thick and loose fibrous capsule formation on day 7 and was replaced by thin and dense fibrous capsule formation finally Cintra et al, 2013;Taha et al, 2016;Bueno et al, 2019 • The thickness of fibrous capsules increased over time Khalil and Abunasef, 2015 • Dystrophic calcification and birefringent structure Viola et al, 2012;Cintra et al, 2013;Hinata et al, 2017;Bueno et al, 2019 • Enhanced M2 macrophage polarization Ito et al, 2014 Mouse • Induced the acute inflammation and biomineralization simultaneously Reyes-Carmona et al, 2010 Bioaggregate Rat • Less inflammatory response and produce less calcification compared to MTA Batur et al, 2013 • More inflammatory response compared to MTA Saghiri et al, 2013b • Similar biocompatibility to MTA Bosio et al, 2014 • Adverse effect on liver function and kidney function Khalil and Eid, 2013;Simsek et al, 2016 Biodentine Rat • Intense inflammation on day 7 and decreased over time Mori et al, 2014;Pinheiro et al, 2018 • Fibrous capsules formation Da et al, 2016Da et al, , 2019…”
Section: Bioaggregatementioning
confidence: 99%